2010
DOI: 10.1016/j.surfcoat.2010.10.038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and electrical characterisation of a phase transformation in thermal barrier coatings

Abstract: The electrical and mechanical properties of atmospheric plasma sprayed (APS) yttria stablised zirconia (YSZ) thermal barrier coatings (TBCs) were determined using impedance spectroscopy and an indentation technique, respectively. Upon thermal exposure, sintering and phase transformation occurs in the YSZ TBCs, leading to changes in both the mechanical and electrical properties of the TBCs. After the thermal treatment, the formation of the monoclinic phase in the YSZ TBCs reduced the density of the TBCs and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…14 Based on the results of the Part-I, 14 the durations of stage I at 1000°C and 1300°C were approximately 50 hours and 10 hours, respectively. However, the significant formation of monoclinic phase often needs a much longer incubation period (e.g., 100-150 hours at 1300°C [30][31][32] ). Therefore, it is reasonable to conclude that the sintering at stage I is relatively unaffected by the phase change.…”
mentioning
confidence: 99%
“…14 Based on the results of the Part-I, 14 the durations of stage I at 1000°C and 1300°C were approximately 50 hours and 10 hours, respectively. However, the significant formation of monoclinic phase often needs a much longer incubation period (e.g., 100-150 hours at 1300°C [30][31][32] ). Therefore, it is reasonable to conclude that the sintering at stage I is relatively unaffected by the phase change.…”
mentioning
confidence: 99%
“…The sequential growth with correspondence C provided direct proof of the phenomenological theory. In addition, correspondence A was also observed frequently in partially-transformed grains, while it was rotated along the shear direction [1][2][3][4][5][6][7][8][9][10] t to an atypical A form. This hindered the self-accommodation process due to the large lattice mismatch.…”
Section: Discussionmentioning
confidence: 99%
“…8 Over the last several decades, the experimental characterization of monoclinic variant features has been one of the main challenges in the analysis of YSZ. The transformation generally occurs on the nanoscale and the size of the monoclinic variants is of the order of tens of nanometers, while Raman spectroscopy, 9 X-ray diffraction, 10 and neutron scattering 11 can only measure macroscopic features. Transmission electron microscopy (TEM) can observe the variants with nanoscale resolution.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the sintering of APS coatings mainly focuses on the evolution of thermodynamic parameters of coatings with sintering time [6][7][8][9][10]. Based on experimental observations of microstructure evolution of APS coatings during sintering [11][12][13], Siebert et al found that the formation of an interlaminar sintered neck would increase the Young's modulus of the coating, and no phase change would occur in this process [14][15][16]. The experiments of Hardwicke et al showed that the formation of a sintered neck strengthened the heat transfer between plates and thus increased the thermal conductivity of the coating [17][18][19].…”
Section: Introductionmentioning
confidence: 99%